2008
DOI: 10.1111/j.1399-302x.2008.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of oral anaerobic bacteria cultivated from subgingival biofilm by MALDI‐TOF‐MS

Abstract: Our results suggest that MALDI-TOF-MS might become a useful method for the identification of anaerobic bacteria, especially for those that cannot be readily identified by biochemical analysis. It may become an attractive system even for the routine identification of clinical isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 22 publications
0
43
0
1
Order By: Relevance
“…A database was created, and analysis of results revealed identifications consistent with phenotypic and 16S rRNA gene sequencing data. The technology was able to differentiate between two species of Prevotella, P. intermedia and P. nigrescens, a task which would usually be relegated to costly and time-consuming 16S rRNA gene analysis (245).…”
Section: Anaerobic Bacteriamentioning
confidence: 99%
“…A database was created, and analysis of results revealed identifications consistent with phenotypic and 16S rRNA gene sequencing data. The technology was able to differentiate between two species of Prevotella, P. intermedia and P. nigrescens, a task which would usually be relegated to costly and time-consuming 16S rRNA gene analysis (245).…”
Section: Anaerobic Bacteriamentioning
confidence: 99%
“…Several studies have also investigated subsets of organisms, such as difficult-to-identify Nocardia spp., anaerobes, and oral flora, as well as fastidious upper respiratory flora (e.g., Neisseria spp., Moraxella spp., Haemophilus spp.) (5,9,12,13,15,16). Haemophilus spp., including H. influenzae, were previously shown to be distinguishable by MALDI-TOF MS (5), and since H. influenzae and HACEK organisms have similar growth requirements, this suggested that MALDI-TOF MS may be useful in their identification.…”
mentioning
confidence: 99%
“…Indeed, mass spectra (m/z range between 2000 and 13000) obtained for A. schaalii strains appear to be unique and reproducible. Notingly, all the databases now available do not include the spectrum profile for this species and must be updated (11,17).…”
Section: Introductionmentioning
confidence: 99%